Enhancing Marketing Efficiency through Agility in the Telecommunications Sector: The Case of Asia Cell in Baghdad: Meningkatkan Efisiensi Pemasaran melalui Ketangkasan di Sektor Telekomunikasi: Kasus Asia Cell di Baghdad - Hasan, Marwan Sabah; Al-Dulaimi, Zaid Yaseen Saud (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
This study examines the role of agile marketing in enhancing marketing efficiency within the telecommunications sector, specifically focusing on Asia Cell in Baghdad, Iraq. Addressing a critical theoretical gap, this research explores key dimensions of agile marketing—including iterative experimentation, cost efficiency in core operations, and enhanced communication dynamics—and their strategic implementation in emerging markets. Employing a quantitative approach, data were collected from 104 respondents to analyze the impact of agile marketing practices on overall marketing efficiency. The findings indicate that agile marketing significantly improves operational effectiveness and responsiveness, providing valuable insights for telecommunications companies aiming to thrive in competitive environments.